2004
DOI: 10.1007/s00277-004-0914-3
|View full text |Cite
|
Sign up to set email alerts
|

Extranodal marginal zone B-cell lymphomas of mucosa-associated lymphoid tissue?type of the orbit and ocular adnexa

Abstract: Non-Hodgkin's lymphomas of the orbit and ocular adnexa (OOA), the majority of which are extranodal marginal zone B-cell lymphomas of mucosa-associated lymphoid tissue-type (MALT lymphomas), are a rare disorder. The aim of this study was to evaluate the clinical features and treatment outcomes and complications in patients with MALT lymphoma of OOA. Thirty-seven patients with a histologically verified diagnosis of MALT lymphoma of OOA were included in this retrospective, observational case study. There were 22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 27 publications
7
67
1
Order By: Relevance
“…Several publications have reported a total of 80 patients in whom no complementary treatment, and particularly no radiotherapy, was performed after surgical excision. 11,13,18,36,37,39,42,44,45,47,91 Some of these studies indicated that local relapse occurred more frequently after simple surgical excision than after radiotherapy. 18,42 However, this approach has not been fully evaluated; the outcome was clearly indicated for only 8 patients in these reports.…”
Section: Surgical Excision and Wait-and-see Policymentioning
confidence: 99%
See 2 more Smart Citations
“…Several publications have reported a total of 80 patients in whom no complementary treatment, and particularly no radiotherapy, was performed after surgical excision. 11,13,18,36,37,39,42,44,45,47,91 Some of these studies indicated that local relapse occurred more frequently after simple surgical excision than after radiotherapy. 18,42 However, this approach has not been fully evaluated; the outcome was clearly indicated for only 8 patients in these reports.…”
Section: Surgical Excision and Wait-and-see Policymentioning
confidence: 99%
“…37 A number of studies 11,13,18,16,27,30,36,39,[41][42][43][44][45][46][47]83,91 have reported treatment with chemotherapy alone or in combination with other modalities, but few have reported the response rates obtained with these treatments. 11,46,47,84,85 Lee et al 47 reported 3 patients who underwent CHOP chemotherapy, 2 of whom experienced complete remission. Sasai et al 46 observed no significant difference in cause-specific or overall survival rates for patients with MALT lymphoma treated with radiotherapy alone or with exclusive single-agent or combination chemotherapy.…”
Section: Chemotherapy Regimens and Oalmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite resolution of the tumor after irradiation, supraduction limitation was not improved, suggesting that irradiation led not only to tumor cell death, but also subsequent irreversible muscle fibrosis. It was previously reported that the most common site of ocular EMZL was the conjunctiva (51%), while extraocular muscles were the most rare localization (only 5%) (1). A review the literature revealed only 9 cases of orbital lymphoma invading the superior rectus muscle, in which, histologically, EMZL was not included (2-5) (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…This case was an EBV-negative lymphoma and the disease extent was limited to the eye; therefore, we decided that a local radiotherapy would be the treatment modality because radiotherapy is one of the competent options among the treatment modalities for orbital MALT lymphoma (21)(22)(23)(24)(25). Recent studies reported that a radiotherapy dose range of 25∼35 Gy achieved ex-cellent survival rates for stage IEA orbital MALT lymphoma (26). In addition, we changed tacrolimus to sirolimus for its anti-proliferative effect.…”
Section: Case Reportmentioning
confidence: 99%